Cluster-randomised non-inferiority trial comparing DVD-assisted and traditional genetic counselling in systematic population testing for BRCA1/2 mutations. Issue 7 (18th March 2016) - Manchanda, Ranjit; Burnell, Matthew; Loggenberg, Kelly; Desai, Rakshit; Wardle, Jane; Sanderson, Saskia C; Gessler, Sue; Side, Lucy; Balogun, Nyala; Kumar, Ajith; Dorkins, Huw; Wallis, Yvonne; et al.
Abstract : Background: Newer approaches to genetic counselling are required for population-based testing. We compare traditional face-to-face genetic counselling with a DVD-assisted approach for population-based BRCA1/2 testing. Methods: A cluster-randomised non-inferiority trial in the London Ashkenazi Jewish population. Inclusion criteria: Ashkenazi Jewish men/women >18 years; exclusion criteria: (a) known BRCA1/2 mutation, (b) previous BRCA1/2 testing and (c) first-degree relative of BRCA1/2 carrier. Ashkenazi Jewish men/women underwent pre-test genetic counselling prior to BRCA1/2 testing in the Genetic Cancer Prediction through Population Screening trial (ISRCTN73338115 ). Genetic counselling clinics (clusters) were randomised to traditional counselling (TC) and DVD-based counselling (DVD-C) approaches. DVD-C involved a DVD presentation followed by shorter face-to-face genetic counselling. Outcome measures included genetic testing uptake, cancer risk perception, increase in knowledge, counselling time and satisfaction (Genetic Counselling Satisfaction Scale). Random-effects models adjusted for covariates compared outcomes between TC and DVD-C groups. One-sided 97.5% CI was used to determine non-inferiority. Secondary outcomes: relevance, satisfaction, adequacy, emotional impact and improved understanding with the DVD; cost-minimisation analysis for TC and DVD-C approaches. Results: 936 individuals (clusters=256, mean-size=3.6) were randomised to TC (n=527, clusters=134) and DVD-C (n=409, clusters=122) approaches. Groups were similar at baseline, mean age=53.9 (SD=15) years, women=66.8%, men=33.2%. DVD-C was non-inferior to TC for increase in knowledge (d=−0.07; lower 97.5% CI=−0.41), counselling satisfaction (d=−0.38, 97.5% CI=1.2) and risk perception (d=0.08; upper 97.5% CI=3.1). Group differences and CIs did not cross non-inferiority margins. DVD-C was equivalent to TC for uptake of genetic testing (d=−3%; lower/upper 97.5% CI −7.9%/1.7%) and superior for counselling time (20.4 (CI 18.7 to 22.2) min reduction (p<0.005)). 98% people found the DVD length and information satisfactory. 85–89% felt it improved their understanding of risks/benefits/implications/purpose of genetic testing. 95% would recommend it to others. The cost of genetic counselling for DVD-C=£7787 and TC=£17 307. DVD-C resulted in cost savings=£9520 (£14/volunteer). Conclusions: DVD-C is an effective, acceptable, non-inferior, time-saving and cost-efficient alternative to TC. Trial registration number: ISRCTN 73338115.